932 A Systematic Review and Meta-Analysis of Subxiphoid Versus Unilateral Intercostal Video-Assisted Thoracoscopic Surgery. (4th May 2021) - Patel, D; Almukhtar, A; Caruana, E
Abstract: Introduction: Subxiphoid approach is emerging as an alternative to intercostal video-assisted thoracoscopic surgery (VATS). We sought to compare the clinical efficacy of both approaches. Method: A protocol was registered at PROSPERO [CRD42020155686]. Studies were retrieved from literature in July 2020. The Main outcomes were operative duration, intraoperative complications and postoperative length of hospital stay (LoS). Subgroup analysis was performed by procedure type. Results: 1469 patients (51% male) were included from 12 observational studies, with 620 (42%) having undergone sVATS. There was a high-moderate risk of bias across included papers. There was no difference in operative duration (MD 13.1 minutes, 95% CI -11.3 to + 37.6; p = 0.29), intraoperative complications (OR 0.17, 95% CI -0.28 to + 0.61; p = 0.47), or LoS (MD -0.8 days, 95% CI -1.8 to + 0.2; p = 0.08). LoS was lower for sVATS thymectomy (MD -1.7 days, 95% CI -2.9 to -0.3; p = 0.01). Acute pain (10-point numerical rating scale) was lower for sVATS (MD -2.2, 95% CI -3.2 to -1.2; p < 0.001). There was insufficient data to report on chronic pain, quality of life, or surgeon workload. Conclusions: There is a potential benefit for sVATS in selected procedures. Well-designed randomised trials with consistent outcome reporting are required.